Hak Milik Intelektual dalam Pandangan Hukum Islam - Drs. Agus Triyanta, M.A., M.H., Ph.D (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The right according to Islamic jurisprudence permit the limitation exclusive owner Isike copyright, but Islamic forbid it ifthat reason then group ofpeople 'let' the others in ignorance because oftheir poverty, so they are not be able to pay with high price for knowledge and discovery, whereas it iscrucial for him in abandoning their poverty and ignorance. In this case, the justice and social principles in implementing intellectual copyright have to be extended more.